Preconditions of Formation of Lithuanian Schoolchildren’s Citizenship and National Identity - Ranonytė, Asta (Acta Paedagogica Vilnensia, 2006)
National identity and citizenship are the most significant phenomena in the context of European integration. The text of this article reveals the main components of these two concepts and describes social, political, cultural and historical factors which influence the formation and the expression of citizenship and national identity The theoretical background and empirical study of pupils at the age of 17 provide the opportunity to analyse the relationship between civic attitudes and national identity, to characterise the main differences of perception of these phenomena among the ethnic groups of Lithuanian, Russian and Polish pupils.